Comparison of an exergame and a moderate-intensity endurance training intervention on physiological parameters - Schürch, Yannik; Burger, Manuel; Amor, Lauren; Zehnder, Cäcilia; Benzing, Valentin; Mieschler, Mélanie; Baur, Heiner; Schmid, Stefan; Bangerter, Christian; Nigg, Claudio R.; Ketelhut, Sascha (Current Issues in Sport Science (CISS), 2023)
Background Exergames are interactive video games that stimulate an active, whole-body gaming experience (Best, 2013). By combining electronic entertainment with physical exercise, exergames offer novel opportunities to expand physical activity in different age groups and settings. Even though studies have found a significant increase in energy expenditure when playing exergames compared to normal video games, most games only induce low to moderate-intensity activity which is too low to result in relevant physical adjustments (Biddiss & Irwin, 2010). This study assessed the effects of an 8-week exergame-training (EXT) in an innovative exergame called the ExerCube and compared it with a typical moderate-intensity endurance training (ET) intervention. Methods In total, 19 individuals (10 female; age 26.9 ±8.7 years; body mass index (BMI) 23.6 ±3.1 kg/m2) participated and were block randomized into an EXT group (n = 9) and an ET group (n = 10). Throughout the 8-week intervention period, the EXT group attended 20-30-minutes of EXT three times a week while the ET group completed 15-45-minutes of ET (jogging/cycling at 65-75% of maximal heart rate) three times a week. Before and after the intervention BMI, systolic and diastolic blood pressure, and VO2max (spiroergometry; start: 50 or 75 W; increment: 25 W/min) were assessed and compared (paired-samples t-test, ANOVA). Results Significant time × group interaction effects were found for VO2max (F(1,17) = 11.345; p = .004, ηp2 = .400). The EXT group revealed significant within-group effects in VO2max from pre (43.2 ±10.6 ml/kg*min) to post (46.9 ±10.9 ml/kg*min; p = .004, d = 1.308) while the ET group revealed no significant changes (pre: 39.4 ±5.4 ml/kg*min; post: 39.7 ±4.9 ml/kg*min; p = .466, d = .241). No significant time × group interaction effects were detected in systolic blood pressure (F(1,17) = .050; p = .825, ηp2 = .003) or diastolic blood pressure (F(1,17) = .005; p = .943, ηp2 = .000). However, there was a significant decrease in the peripheral systolic blood pressure from pre (122 ±10 mmHg) to post (117 ±12 mmHg; p = .034, d = .792) in the ET group but not in the EXT group (pre: 118 ±8; post: 114 ±7; p = .156, d = .523). Concerning BMI, no significant interaction effects (F(1,17) = 2.818; p = .111, ηp2 = .142) were detected. Conclusions The EXT seems to be more effective as conventional ET exercise approach to improve endurance performance. This is promising as exergame may develop intrinsic motivation/enjoyment for physical activity. Further studies confirming these findings and extending to psychological variables are needed. References Best, J. R. (2013). Exergaming in youth: Effects on physical and cognitive health. Zeitschrift für Psychologie, 221(2), 72-78. https://doi.org/10.1027/2151-2604/a000137 Biddiss, E., & Irwin, J. (2010). Active video games to promote physical activity in children and youth: A systematic review. Archives of Pediatrics & Adolescent Medicine, 164(7), 664-672. https://doi.org/10.1001/archpediatrics.2010.104